2004
DOI: 10.1074/jbc.m404671200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Activation of Endogenous Transporters in Xenopus laevis Oocytes Expressing the Plasmodium falciparum Chloroquine Resistance Transporter, PfCRT

Abstract: A large body of genetic, reverse genetic, and epidemiological data has linked chloroquine-resistant malaria to polymorphisms within a gene termed pfcrt in the human malarial parasite Plasmodium falciparum. To investigate the biological function of the chloroquine resistance transporter, PfCRT, as well as its role in chloroquine resistance, we functionally expressed this protein in Xenopus laevis oocytes. Our data show that PfCRT-expressing oocytes exhibit a depolarized resting membrane potential and a higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 66 publications
3
48
1
Order By: Relevance
“…While the discovery [5] and subsequent study [see for review 11] of the pfcrt gene has added much to our understanding of the molecular mechanism of CQ resistance in malaria, neither the endogenous function, nor the physiological mechanism by which pfcrt confers CQ resistance are clear. Heterologous expression of PfCRT in Pichia pastoris, Saccharomyces cerevisiae [23,24], Dictyostelium discoides [18] and Xenopus laevis [25] has shown that the protein is more amenable to biochemical and physiological analysis in less technically onerous systems than P. falciparum. We chose the HEK293 cell line for heterologous expression, as it is widely used for functional studies of cellular physiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the discovery [5] and subsequent study [see for review 11] of the pfcrt gene has added much to our understanding of the molecular mechanism of CQ resistance in malaria, neither the endogenous function, nor the physiological mechanism by which pfcrt confers CQ resistance are clear. Heterologous expression of PfCRT in Pichia pastoris, Saccharomyces cerevisiae [23,24], Dictyostelium discoides [18] and Xenopus laevis [25] has shown that the protein is more amenable to biochemical and physiological analysis in less technically onerous systems than P. falciparum. We chose the HEK293 cell line for heterologous expression, as it is widely used for functional studies of cellular physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological and biochemical studies of Plasmodium proteins in situ are time consuming and subject to technical barriers [22]. Heterologous expression offers a more convenient system to study PfCRT and to investigate its interactions with drugs [18,[23][24][25]. Here, we demonstrate robust expression of full length PfCRT in human embryonic kidney (HEK293) cells.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The prospect that AeNHE8 is contained in vesicles that fuse with the plasma membrane under conditions of diuresis was ruled out by feeding mosquitoes a blood meal and application of dibutyryl-cAMP to isolated tubules, both of which stimulate Na + excretion but did not alter the localization of the transporter. Efforts to characterize the exchanger that was expressed heterologously in Xenopus laevis oocytes by twoelectrode voltage clamp techniques were frustrated by the activation of well known Na + conductances (Nessler et al, 2004;Reifarth et al, 1999;Tzounopoulos et al, 1995 (Rheault et al, 2007) makes NHAs even more attractive because they could use the high apicalmembrane voltage that is established by the H + V-ATPase (Day et al, 2008).…”
Section: Mosquito Nhes Are Not Electrophoretic Plasma Membrane Proteinsmentioning
confidence: 99%
“…PfCRT-expressing oocytes exhibit a depolarized membrane potential (⌿ m ) and a higher intracellular pH (pH i ) compared to control oocytes (9). One possibility is that PfCRT interferes with second messengers such as Ca 2ϩ (9).…”
mentioning
confidence: 99%